2006
DOI: 10.1016/j.juro.2006.07.140
|View full text |Cite
|
Sign up to set email alerts
|

Radical Prostatectomy After Previous Prostate Surgery: Clinical and Functional Outcomes

Abstract: Radical retropubic prostatectomy can be performed safely after previous prostate surgery for bladder outlet obstruction. However, a consistent surgical background in prostate surgery is needed to manage frequently unexpected difficulties. Candidates for second line prostate surgery should be informed that functional results are less predictable and satisfactory than those achieved after the same surgical approach in naïve patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
2
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 19 publications
2
86
2
8
Order By: Relevance
“…A number of technical points need to be considered before embarking on radical prostatectomy following TURP. First, Colombo et al 49 reported that the dissection and preservation of the urethral stump integrity constantly appeared the most difficult step in open surgery. Some investigators report that periprostatic fibrotic tissue renders the nerve-sparing procedure a difficult task; 45,49 however Eden et al 50 did not report the same difficulty.…”
Section: Robotic Surgery Following Turpmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of technical points need to be considered before embarking on radical prostatectomy following TURP. First, Colombo et al 49 reported that the dissection and preservation of the urethral stump integrity constantly appeared the most difficult step in open surgery. Some investigators report that periprostatic fibrotic tissue renders the nerve-sparing procedure a difficult task; 45,49 however Eden et al 50 did not report the same difficulty.…”
Section: Robotic Surgery Following Turpmentioning
confidence: 99%
“…Finally, residual prostatic tissue could only be removed en bloc in 28% of cases. 49 How LRP or open prostatectomy following TURP compare to RARP remains to be answered. At present a number of groups 45,51 recommend performing LRP after at least 3 months after TURP and there is no reason to believe that this would not be a reasonable interval in RARP.…”
Section: Robotic Surgery Following Turpmentioning
confidence: 99%
“…Radical prostatectomy for incidental prostate cancer, open or laparoscopic, is reported to have satisfactory oncologic outcome but functional outcome is inferior compared with the patients without history of TURP [7][8][9][10][11]. Thus, in the management of incidental prostate cancer, postoperative morbidities resulted from probable overtreatment might become more important compared with T1c cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Los pacientes con obesidad y próstata de grandes dimensiones, como el paciente intervenido en nuestra institución, pueden necesitar intervenciones con duraciones significativamente más largas [20][21][22] . Los pacientes que han sido sometidos a cirugía de próstata anteriormente también pueden necesitar intervenciones más largas 23 .…”
Section: Duración Prolongada De La Intervenciónunclassified